ANALISIS BEBAN KERJA DAN JUMLAH OPERATOR PENULANGAN RANGKA BETON UDIT - Wahyuni, Dini; Sembiring, Meilita Tryana; Putra, Suryadi; Budiman, Irwan (CANTILEVER, 2019)
This study was conducted at a factory producing construction and building materials such as ready mix concrete, piles, udit concrete, and ryol.  These products are produced in almost the same process, but on different production lines.  There are 2 operators in the frame reinforcement section for udit concrete production.  It is seen that the two operators have the same task but different results of their work, so that the production target is not achieved.  The workload analysis method is used to determine the operator's actual load.  Observation of activities is carried out by the work sampling method for 5 days.  In work sampling, work and idle activities of workers are observed at randomly selected times and the amount of production during observations is recorded.  From the study, it is known the ideal of actual load of each operator and the number of operators for the concrete frames reinforcement.  The results showed workload of operator 1 was 95.11% while workload of operator 2 was 107%.  The number of operators reinforcing concrete frames remains fixed for 2 people, but wage compensation needs to be given to operators 2 for excess workload refers to the amount of wages and provisions for overtime that are applicable in the company.